Exploratory analysis of poultry workers’ knowledge and practices Regarding highly pathogenic avian influenza in Guinea - Maladho Diaby; Salifou Talassone Bangoura; Castro Gbêmêmali Hounmenou; Kadio Jean-Jacques Olivier Kadio; Aly Badara Touré; Kouramoudou Bereté; Emile Faya Bongono; Sidikiba Sidibé; Alexendre Delamou; Alioune Camara; Alpha-Kabinet Keita; Abdoulaye Touré (PLoS ONE, 2025)
Background In 2022-2023, Guinea experienced a major avian influenza epizootic, leading to significant economic losses and increasing the risk of transmission to humans. Raising awareness and promoting protective behaviour among the general population, particularly high-risk groups, could help strengthen prevention and control measures for this zoonosis. This study aimed to assess knowledge and practices related to avian influenza among poultry workers in Guinea. Methods A cross-sectional study was conducted between November and December 2023 on poultry farms in Coyah and Forecariah, Guinea prefectures. A survey was administered to all poultry farms in these two prefectures. Data were collected using a questionnaire, which included the following variables: socio-demographic and professional profile of respondents, avian influenza information, sources of information, and a series of questions to assess their knowledge and practices. Knowledge and practice scores were then calculated. The cumulative local effects method was used to assess the influence and contribution of each co-variate to changes in the probability of knowledge and practice levels among poultry farm staff. Results A total of 326 poultry workers participated in the survey, including poulterers (62.3%), managers (17.5%), and poultry technicians (13.8%). More than half of these workers (54.9%) had heard of influenza avian. Their primary sources of information were health workers (27.9%), friends and fellow farmers (23.3%) and employees (22.7%). Overall, the knowledge of avian influenza was relatively low among poultry workers (42.9%), and the majority (68.4%) demonstrated poor practices on poultry farms. Analysis using the ALE model reveals that age, education and type of occupation are significantly associated with knowledge. At the same time, the number of farms managed, the number of hours worked, and gender are associated considerably with practices among these workers. Conclusion The study revealed a low level of knowledge and poor practices among poultry farm workers despite an avian flu epizootic. These findings suggest the need for a targeted strategy to prevent the risk of virus transmission to humans, including awareness-raising, training, and providing personal protective equipment.